Neuroticism and fear of COVID-19 during the COVID-19 pandemic: Testing the mediating role of intolerance of uncertainty and sense of control among Chinese high school students - Zhang, Donghuan; Fan, Min; Meng, Lingyi; Zheng, Xifu (Frontiers in Psychology, 2022)
Since the COVID-19 pandemic broke out in 2019, neuroticism has been proved a predictor of fear of COVID-19 infection. But few studies have been conducted researching the factors affecting the relationship between neuroticism and this kind of fear. The aim of the present study was to explore how trait neuroticism influences pandemic fear. A cross-sectional study was conducted in Guangdong and Guangxi province, China, and collected complete datasets from 792 high school students. Our study found that a) individuals with high neuroticism tended to have higher intolerance of uncertainty (IU) and lower sense of control (SOC); b) IU and SOC played a mediating role between neuroticism and fear of COVID-19 and a serial mediation effect was found between these factors; c) after controlling both IU and SOC, the effect of neuroticism on fear was no longer significant. The results suggested a critical role of IU and sense of control in the causal relationship between neuroticism and fear.